The physiological response to increased temperature in over-wintering sea ice algae and phytoplankton in McMurdo Sound, Antarctica and Tromsø Sound, Norway - Martin, A; Andrew McMinn; Heath, M; Hegseth, EN; Ryan, KG (2012)
The physiological response to increased temperature during dark exposure was examined in phytoplankton and sea ice algae that had overwintered in McMurdo Sound, Antarctica and Tromsø Sound, Norway. Under ice phytoplankton and sea ice algae from McMurdo Sound were incubated in the dark for 22 days and 23 days respectively at −2, 4 and 10 °C, while phytoplankton from Tromsø Sound were incubated for 35 days at 4, 10 and 20 °C. A fluorescence approach was used to examine algal photophysiology (Fv/Fm, rETRmax and α) and changes in the concentration of chlorophyll a , while the spectrophotometric 2,4,6-tripyridyl- s -triazine (TPTZ) assay was used to quantify water-extractable carbohydrates. Prior to incubation, the photosynthetic parameters documented relatively healthy overwintering communities for both polar regions. Elevated temperature had a considerable impact on the dark survival of Arctic phytoplankton, and, to a lesser extent, Antarctic sea ice algae: photosynthetic health and stored monosaccharides declined during the incubation period, particularly at the warmest temperature regimes. In contrast, the concentration of chlorophyll a and polysaccharides remained relatively constant. When Antarctic sea ice algae were subsequently exposed to low light (~ 20 μmol photons m − 2 s − 1 ), significant photosynthetic recovery was only observed in cultures maintained at −2 °C. A more robust response to increased temperature was observed in Antarctic phytoplankton and in general, variability between the −2 °C and 4 °C (Antarctic) and 4 °C and 10 °C (Arctic) temperature regimes was minimal, which suggests that increasing temperature will not limit the ability of phytoplankton to survive the polar winter and provide the inocula for bloom events.